Infrastructure violence and retroliberal development: connectivity and dispossession in Laos. Issue 8 (22nd July 2021) - Sims, Kearrin
Abstract: This article examines the centrality of infrastructure connectivity within the post-2008 'retroliberal' global aid regime. Through the critical interrogation of connectivity and development discourse within Southeast Asia, as well as longitudinal field research examining repeated bouts of dispossession in Laos, I argue that all Southeast Asian states, regionally operating multilateral development banks and leading regional bilateral aid providers consider transnational infrastructure connectivity essential to development. Following this, I contend that large-scale infrastructure projects frequently increase disadvantaged communities' exposure to intersectional forms of structural violence, epistemic violence, slow violence and infrastructural violence. Having made these arguments, I suggest that the normalisation of infrastructure connectivity as constitutive of development is producing increasingly violent development outcomes, and that intersectional interrogations of infrastructure violence are needed to better understand such outcomes. The argument presented is based on more than 20 months of in-country fieldwork in Laos and 40 interviews with 18 displaced residents. Fieldwork commenced in 2009 and remains ongoing.